Multikulturisme dan Pendidikan Multikultural - Munawir Haris (LPPM IAIN Sorong, 2015)
The plurality must be done in the world. The nature of religion has been endlessly discussed by philosophers, theologians, psychologists, and sociologists. They look at different aspects of religion as their interests and their purposes differ. Therefore, they formulate variety of definition of religion. Religion is seen to be difficult to define. But it is necessary to have a clear definition of religion as a starting point for religious studies. This paper discusses the definitions of religion given by the scholars and then gives a clear definition as an attempt to build up tolerant. Religion is not the same with religious beliefs and practices or religious experiences. So this article discusses about that